Constructing the divine - Chophy, G. Kanato, author.
1 online resource.
Keywords: From being characterized as 'primitive tribe' in the colonial imagination to become predominantly practitioners of the American Baptist faith, the Sumi Naga - formerly known as the Sema Naga- in the North-East Indian state of Nagaland have come a long way ever since this Naga tribe encountered the white man toward the latter half of the nineteenth century.This book in a way chronicles the transition of Sumi society from the period of colonial contact up to the present-day context. A critical understanding of Sumi society and culture is at the heart of the narrative, and the analysis of Sumi religion and world view remains the main thrust of this book. It is argued that the Sumi, who are overwhelmingly Baptists, are faced with new religious issues which has brought about not only schismatic divisions but also rendering ebullience to religious life, and that a new discourse has emerged in Sumi religion. The author positions himself as an 'insider', and in doing so has given a reflexive account of Sumi religious life, meanwhile substantiating the arguments and findings in the light of contemporary theoretical developments. The volume brings out compelling evidence that religion significantly shapes the daily life of the Sumi. It offers a detailed ethnographic study of Sumi religion and world view, as the Sumi Naga was seldom studied in-depth in the post-Independence period. Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka